The Use of Affixed Words in BIPA Student Writing Beginner Class - Candra Ayu Dyah Khoirun Nisa' (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2022)
Indonesian is a second language for BIPA students and should be learned after the primary language. This leads to differences in the understanding  of linguistic structures focused on the order of affixes. This research aims to describe the use of affixed words and the errors of words with affixes in the essays of beginner class BIPA students at the University of Muhammadiyah Malang. The method used in this research is a qualitative method with a descriptive type of research. The source of the data used is a narrative text compiled by students of BIPA University of Muhammadiyah Malang for beginner class. The data used in this research are words with affixes with both appropriate and inappropriate use in BIPA students’ essays. In this research, reading and note-taking techniques were used for data collection. The technique used to analyze the data in this research is replacement technique. Based on the result of the study, it can be concluded that there are three forms of affixes in BIPA students’ essays, including 118 data prefixes, 66 data confixes, and 38 data suffixes. In this case, three types of affixation errors were also found, including the omission of affixes as much as 7 data, replacement of morphs as much as 2 data, and the use of incorrect affixes as many as 26 data. This research can be used as a reference for further research, and as information for readers, especially BIPA students and teachers, to use correct Indonesian grammar.